Pakistan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues and Statistical Appendix paper presents cross-country regression results that identify investment in physical capital and improvements in institutional quality as having the largest pay-off in terms of increased growth. The paper employs three approaches to forecast inflation in Pakistan. A leading indicator model outperforms a univariate autoregressive moving average model as well as a vector autoregressive model in terms of forecast quality. The paper presents three case studies of Pakistani public sector enterprises that have recently witnessed strong improvements in their financial performance.